Are deep-sea ecosystems surrounding Madagascar threatened by land-use or climate change?. (January 2018) - Fontanier, Christophe; Mamo, Briony; Toucanne, Samuel; Bayon, Germain; Schmidt, Sabine; Deflandre, Bruno; Dennielou, Bernard; Jouet, Gwenael; Garnier, Eline; Sakai, Saburo; Lamas, Ruth Martinez; Duros, Pauline; et al.
Abstract: In this short communication, we present a multidisciplinary study of sedimentary records collected from a deep-sea interfluve proximal to the mouths of major northwestern Madagascan rivers. For the last 60 years, the seafloor has been repeatedly disturbed by the deposition of organic rich, tropical, terrestrial sediments causing marked reductions in benthic biodiversity. Increased soil erosion due to local land-use, deforestation and intensifying tropical cyclones are potential causes for this sedimentary budget and biodiversity shift. Our marine sedimentary records indicate that until now, these conditions have not occurred within the region for at least 20, 000 years. Highlights: Since the 1950s, the seafloor off NW Madagascar has been disturbed by terrestrialsediments. This abrupt sedimentary change has caused marked reductions in benthic biodiversity. Land-use, deforestation and intensifying tropical cyclones are potentialcauses of soil erosion.